Calling for a meaningful contribution? Bridging contributing to society with motivation theory - Bryant, Rowdy; Lysova, Evgenia I.; Khapova, Svetlana N. (Frontiers in Psychology, 2023)
This paper examines the concept of “contributing to society” in the context of meaningful work and calling. While previous studies have identified it as a significant dimension within these concepts, little attention has been paid to trying to conceptualize it. Also, with “self-oriented” fulfillment being an important aspect of the experience of meaningfulness, the understanding of contribution to society might be more complex than being simply an “other-oriented” concept. In response to this conceptual unclarity, we define contributing to society as a belief individuals hold about whether tasks positively impact work beneficiaries. We integrate this with Situated Expectancy-Value Theory (SEVT) to determine the expected task value of such belief. Our argument is that fulfillment of a contribution depends on three factors: (1) the expectation of a contribution based on someone's calling and expected meaningfulness; (2) the extent to which the employee is invested in the task, the costs of such task, whether the beneficiary and impact value and the utility for the self and beneficiary match the preference; (3) the extent to which this contribution is sufficient considering someone's expectation. Therefore, the expected task value can differ between individuals concerning the number and types of beneficiaries and the extent and value of the impact. Moreover, in this way contributions to society should also be perceived from a self-oriented perspective to be fulfilling. This original concept offers a theoretical framework and a research agenda that proposes new avenues of inquiry for calling, meaningful work, contributing to society, and related fields such as job design, and public policy.